Biosurfactant as a promoter of methane hydrate formation: thermodynamic and kinetic studies - Arora, Amit; Cameotra, Swaranjit Singh; Kumar, Rajnish; Balomajumder, Chandrajit; Singh, Anil Kumar; Santhakumari, B.; Kumar, Pushpendra; Laik, Sukumar (Scientific Reports, 2016)
Natural gas hydrates (NGHs) are solid non-stoichiometric compounds often regarded as a next generation energy source. Successful commercialization of NGH is curtailed by lack of efficient and safe technology for generation, dissociation, storage and transportation. The present work studied the influence of environment compatible biosurfactant on gas hydrate formation. Biosurfactant was produced by Pseudomonas aeruginosa strain A11 and was characterized as rhamnolipids. Purified rhamnolipids reduced the surface tension of water from 72 mN/m to 36 mN/m with Critical Micelle Concentration (CMC) of 70 mg/l. Use of 1000 ppm rhamnolipids solution in C type silica gel bed system increased methane hydrate formation rate by 42.97% and reduced the induction time of hydrate formation by 22.63% as compared to water saturated C type silica gel. Presence of rhamnolipids also shifted methane hydrate formation temperature to higher values relative to the system without biosurfactant. Results from thermodynamic and kinetic studies suggest that rhamnolipids can be applied as environment friendly methane hydrate promoter.

Effect of different fixed bed media on the performance of sodium dodecyl sulfate for hydrate based CO2 capture - Arora, Amit; Kumar, Asheesh; Bhattacharjee, Gaurav; Kumar, Pushpendra; Balomajumder, Chandrajit (Materials & Design, 2016)
Sodium Dodecyl Sulfate (SDS) is used as a kinetic promoter in gas hydrate formation. In this work, the performance of SDS for carbon dioxide gas hydrate formation in two different fixed bed media: silica sand and zeolite (5A and 13X) has been evaluated. The concentration of SDS was fixed at 0.5 wt%. The experiments were carried out in batch mode with the initial pressure fixed at 3.0 MPa, and the temperature kept constant at 274.65 K. The results showed that hydrate of carbon dioxide with fixed bed of silica sand was significantly promoted by the addition of SDS as compared to the other fixed bed medium used in this study: zeolite 13X. (c) 2015 Elsevier Ltd. All rights reserved.
Keywords: Carbon dioxide; Fixed bed media; Hydrate formation; Kinetic promoter; Silica sand; Zeolite 5A and 13X

Role of Rhamnolipid: A biosurfactant in methane gas hydrate formation kinetics - Arora, Amit; Cameotra, Swaranjit Singh; Kumar, Rajnish; Singh, Anil Kumar; Kumar, Pushpendra; Balomajumder, Chandrajit; Laik, Sukumar (Proceedings of The First International Conference on Recent Advances in Bioenergy Research, 2016)
Naturally occurring methane gas hydrate is a vast source of methane gas which is trapped in crystalline ice-like structure present in permafrost regions and under the sea in outer continental margins. It is purposed that total amount of carbon in the form of methane hydrates is almost twice the carbon content in all the fossil fuel reserves put together, and hence these are supposed to be the future potential energy resource. This paper investigates the laboratory investigations on effect of a biosurfactant rhamnolipid on methane hydrate formation kinetics. Rhamnolipid was produced by Pseudomonas aeruginosa strain A11. The presence of P. aeruginosa has been reported in Gulf of Mexico gas hydrate samples. Biosurfactant reduced the surface tension of water from 72 to 36 mN/m with CMC of 70 mg/L. The biosurfactant dose is studied at two different concentrations in the solution at 100 and 1000 ppm. Kinetic of hydrate formation and growth is compared at 0, 100, and 1000 ppm of rhamnolipid showing that rhamnolipid acts as a hydrate promoter at these concentrations. Thus, small dosages of rhamnolipids produced by P. aeruginosa strain A11 must clearly affect the gas hydrate formation kinetics in natural sites (as in Gulf of Mexico).
Keywords: Induction time; methane hydrate; Potential energy resource; Pseudomonas aeruginosa; Rhamnolipid

Hydrate-based carbon capture process: assessment of various packed bed systems for boosted kinetics of hydrate formation - Arora, Amit; Kumar, Asheesh; Bhattacharjee, Gaurav; Balomajumder, Chandrajit; Kumar, Pushpendra (Journal of Energy Resources Technology-Transactions of the ASME, 2021)
The case for developing novel technologies for carbon dioxide (CO2) capture is fast gaining traction owing to increasing levels of anthropogenic CO2 being emitted into the atmosphere. Here, we have studied the hydrate-based carbon dioxide capture and separation process from a fundamental viewpoint by exploring the use of various packed bed media to enhance the kinetics of hydrate formation using pure CO2 as the hydrate former. We established the fixed bed reactor (FBR) configuration as a superior option over the commonly used stirred tank reactor (STR) setups typically used for hydrate formation studies by showing enhanced hydrate formation kinetics using the former. For the various packing material studied, we have observed silica gel with 100 nm pore size to return the best kinetic performance, corresponding to a water to hydrate conversion of 28 mol% for 3 h of hydrate growth. The fundamental results obtained in the present study set up a solid foundation for follow-up works with a more applied perspective and should be of interest to researchers working in the carbon dioxide capture and storage and gas hydrate fields alike.
Keywords: air emissions from fossil fuel combustion; Carbon dioxide capture; combustion of waste; Fixed bed reactor; fuel combustion; Gas hydrate; hydrates; kinetics; Silica gel

Rhamonolipids produced by Pseudomonas aeruginosa promotes methane hydrates formation in fixed bed silica gel medium - Arora, Amit; Cameotra, Swaranjit Singh; Balomajumder, Chandrajit; Kumar, Rajnish; Singh, Anil Kumar; Santhakumari, B.; Kumar, Pushpendra; Laik, Sukumar (Marine Geophysical Research, 2021)
Natural gas hydrates are seen as an alternative future energy source. They have also been valued for their carbon dioxide capturing capability, gas separation, desalination, natural gas storage and transportation. Developing economical and viable gas hydrate based technology is one of the most promising research areas of present decade. Successful commercialization of gas hydrate based technology is often curtailed due to slow formation rate. The present study evaluates biosurfactant as a kinetic promoter of methane hydrates formation in a fixed bed C type silica gel medium. Biosurfactant was produced by growing Pseudomonas aeruginosa strain A11 in glycerol supplemented mineral salt medium. Biosurfactant characterization with FTIR, NMR and MALDI-TOF spectroscopy reveled it to be a glycolipids type biosurfactant namely rhamnolipids. Saturating C type silica gel with of 100 ppm rhamnolipids solution enhanced the rate of methane hydrates formation by reducing the induction time. Mole of methane consumed and percentage of water to hydrate conversion was observed to be more in 1000 ppm rhamnolipids saturated C type silica gel as compared to quiescent water system and water saturated silica gel system. Overall results suggest that rhamonolipids produced by strain A11 in combination with silica gel can be utilized as environmentally safe kinetic promoter for methane hydrate formation.
Keywords: Biosurfactant; Energy; Glycolipids; Induction time; Kinetic promoter